Driving positive outcomes of financial institutions: corporate social responsibility, employee well-being, and performance in Madagascar - Rakotoarisoa Maminiaina Heritiana Sedera; Mirwan Surya Perdhana; Rakotoarisoa Maminirina Fenitra; Ronaldo Yolanda Putra; Hajaina Ravoaja (Cogent Business & Management, 2024)
Corporate social responsibility has become an important component in assuring business performance and sustainability, and its implication is evident specifically in developing nations. This investigation estimated the influence of corporate social responsibility (CSR) on employees' performance using employees' well-being as a mediating variable. This empirical study uses quantitative methods with data collected through surveys from 296 employees of 6 banks in Madagascar. This study uses convenience sampling techniques, and the proposed conceptual framework was tested using structural equation modeling (SEM). The findings show that corporate social responsibility activities significantly influence employee performance. Also, this study found that employees' well-being contributes to employees' performance. Lastly, the mediating role of employees' well-being was established, and it was significantly mediating the relationship between corporate social responsibility activities and employee performance. These results provide theoretical and practical reference values for CSR managers to improve companies' social engagement and activities as they enhance well-being and performance. Furthermore, this study is among the few papers focusing on the impact of CSR activities on an individual level. Thus, banks should actively undertake CSR practices and optimize employee efficiency and human capital through their activities.
Keywords: 650; Corporate social responsibility; well-being; performance; bank; Madagascar; developing country